Nutrition: The position in English to-day / G. C. M. M'Gonigle - M'Gonigle, G. C. M. (George Cuthberth Mura), -1939 (London : Industrial Christian Fellowship)
1936-11 1936 1930s 15 pages Nutrition THE POSITION IN ENGLAND TO-DAY G.C.M. M'GONIGLE M.D., D.Hy., B.S., D.P.H. Medical Officer of Health, Stockton-on-Tees Author of "Poverty and Public Health" Published by the Industrial Christian Fellowship 4 The Sanctuary, Westminster, London, S.W.1 Price 2d. 15X/2/217/2